COVID-19 and the secret virtual assistants: the social weapons for a state of emergency - Hannah Marston (Emerald Open Research, 2020)
Technologies are ubiquitous in modern Britain, gradually infiltrating many areas of our working and personal lives. But what role can technology play in the current COVID-19 pandemic? At a time when our usual face to face social interactions are temporarily suspended, many of us have reached out to technology (e.g. Skype, WhatsApp, Facebook, Zoom) to help maintain a sense of closeness and connection to friends, family and vital services. One largely unsung technology is the virtual assistant (VA), a cost-efficient technology enabling users to access the Internet of Things using little more than voice. Deploying an ecological framework, in the context of smart age-friendly cities, this paper explores how VA technology can function as an emergency response system, providing citizens with systems to connect with friends, family, vital services and offering assistance in the diagnosis of COVID-19. We provide an illustration of the potentials and challenges VAs present, concluding stricter regulation and controls should be implemented before VAs can be safely integrated into smart age-friendly cities across the globe.